POTENSI Rhodococcus pyridinovorans GLB5 SEBAGAI BIOKATALIS DALAM KONVERSI SENYAWA METHIL SIANIDA DAN PHENIL SIANIDA - Nunik Sulistinah; Rini Riffiani; Bambang Sunarko (BERITA BIOLOGI, 2016)
Nitrile and amide bioconversion have received increasing attention due to their ability to provide a range of commercially important chemicals. The experiment was conducted to investigate the potential of bacterial isolate GLB5 to convert methyl cyanide and phenyl cyanide. The samples were collected from various industrial waste. Selection of isolates to utilize  these substrates as a sole source of energy, carbon and nitrogen was conducted on 96 whell microtitter plates, based on the growth ability using INT (Iodo nitrotetrazolium chloride) reagent. Based on the growth  pattern, it showed that the bacterial isolate GLB5 grew well and it was capable of utilizing  methyl and phenyl cyanide compound as the sole source of carbon and nitrogen.  The isolate GLB5 was isolated from industrial waste of Batik factory in Cirebon, and  identified as Rhodococcus pyridinovorans. Bioconversion of methyl cyanide using whole cells of R. pyridinovorans GLB5 showed that ethanamide (C2H5NO) and ethanoic acid (C2H4O2) were detected. Formation of ethanamide and ethanoic acid as the product of bioconversion, indicated that the nitrile hydratase and amidase enzymes  involved in the bioconversion process. Phenyl carboxamide (C7H7NO) as the product of phenyl cyanide bioconversion was also detected,  although  in  low  concentration. In this study, R. pyridinovorans GLB5 was capable of completely converting 300 mM methyl cyanide to ±  140 mM ethanoic acid in relatively short times (<60 minutes).